Toward the Sustainable Production of Feedstock Chemicals via Olefin Metathesis - Boisvert, Eliza-Jayne (Université d'Ottawa / University of Ottawa, 2025)
The transition to sustainable chemical production requires a shift from petroleum-based feedstocks to renewable resources: terrestrial and aquatic biomass, and waste materials. Efficient catalytic systems are essential to achieving this goal. Olefin metathesis is a key methodology in this context, offering atom-efficient methods for the transformation of renewable chemicals into specialty and value-added products. Despite this transformative potential, large-scale adoption of olefin metathesis is constrained by challenges in catalyst stability and productivity. This thesis explores barriers to the implementation of olefin metathesis for sustainable chemical production and presents strategies to address these challenges. The first focus of this thesis was improving the synthesis of highly productive catalysts that bear cyclic (alkyl)(amino) carbene (CAAC) ligands. Ru-CAAC catalysts are desirable for their breakthrough productivities in olefin metathesis, but the routes by which they are synthesized are plagued by low yields, particularly in the carbene installation step. By isolating problems in carbene generation from potential inefficiencies in carbene complexation to Ru, this work uncovered a previously unrecognized side-reaction in which free CAACs are consumed by a lithium tetrafluoroborate coproduct. Subsequent studies focused on clarifying which of several postulated side-reactions do indeed occur during carbene generation. The primary problem was traced to dimerization via nucleophilic attack of the free CAACs on their iminium salt precursors. These studies revealed the unexpected stability of CAAC carbenes in solution and led to the isolation of the first free CAACs sufficiently small to confer high activity in olefin metathesis. By mapping out the major factors that limit carbene and catalyst yields, this work offers a guide to improved synthetic protocols. Also examined were factors that contribute to catalyst decomposition during metathesis. Catalyst decomposition caused by oxygen, a ubiquitous contaminant, is a challenge for metathesis catalysts based on virtually all transition metals. Ruthenium catalysts constitute an exception: as a class, they have proved oxygen-tolerant to an impressive degree. The present work reveals that this robustness is not invariable. A subset of ruthenium-thiocatecholate catalysts that is employed for stereocontrolled metathesis is shown to undergo very rapid oxidation, leading to loss of the alkylidene ligand as the aldehyde. Decomposition pathways intrinsic to the dominant class of phosphine-free ruthenium catalysts were also re-analyzed. These culminate in nanoparticles as the ultimate decomposition products of the important N-heterocyclic carbene (NHC) catalysts. The NHC-nanoparticles were shown to be highly active in olefin isomerization, the major selectivity-limiting side-reaction in olefin metathesis. In comparison, CAAC catalysts form fewer nanoparticles, and are isomerization-inactive. Nevertheless, they are likewise highly susceptible to bimolecular decomposition. The classical solution to this problem, site-isolation via catalyst immobilization, severely restricts catalyst activity. In a novel approach aimed at preventing bimolecular decomposition while retaining molecular catalysts, the widely-used NHC ligands were redesigned. Functionalizing the carbene ligands with bulky trityl groups at the 'wingtip' positions indeed inhibited degradation and enhanced productivity. The final work in this thesis showcases two advances aimed at renewable applications. The first exploits the trityl catalysts, with their resistance to bimolecular coupling, for the efficient transformation of phenolic stilbenes - a recalcitrant class of compounds found in plant extractives and lignin waste - into high-value products. The second outlines key principles for fluorophore-tagged CAAC catalysts designed for an ambitious goal: transforming unsaturated fatty acids within living extremophilic algae to produce olefin building blocks as sustainable alternatives to petroleum products. A fluorophore with enhanced photostability and improved selectivity for staining algal lipids was identified and integrated into the catalyst structure. While tuning lipophilicity versus water-solubility is required to enable catalyst uptake within living algae, the fluorophore alone suffers no such constraints, and indeed represents a new tool for algal biology. These findings provide insights into front-line challenges in catalyst synthesis, stability, and design for demanding applications, ultimately expanding the scope of olefin metathesis. By identifying side-reactions that limit synthetic yields of CAAC catalysts and elucidating overlooked decomposition pathways and products, these studies pave the way toward application-guided catalyst design. The successful application of robust CAAC and NHC catalysts in renewable applications highlights the potential for sustainable chemical transformations. Collectively, these findings further advance our understanding of catalyst behavior in olefin metathesis, and help lay the groundwork for future innovations to bridge the gap between bench-scale and industrial processes.
Keywords: Catalysis; Metathesis; Sustainable Chemistry; Catalyst degradation